Status gizi berhubungan positif dengan derajat nyeri sendi penderita osteoartritis lutut - Nyoman Kertia (Jurnal Gizi Klinik Indonesia, 2012)
Background: Knee osteoarthritis (OA) is a common disorder that is associated with significant morbidity, disability, and medical costs, particularly in its advanced stages. While the cause of knee OA remains unclear, it has been associated with various risk factors, such as age, sex, genetic predisposition, biomechanical, and obesity. Pain in osteoarthritis occurs due to combination of various factors. Pain significantly increases the medical and non medical cost in OA. Data showed that obesity will increase the mechanical stress and pain of knee OA. However, uncertainty remains regarding potential relationship between body mass index (BMI) and pain in osteoarthritis. Moreover, since obesity is one of modifiable and preventable risk factors for the onset and progression of the disease, it is important to know the correlation between BMI and severity of pain in knee OA.Objectives: To investigate the relationship between body mass index and severity of joint pain in knee osteoarthritis.Methods: A cross sectional study was conducted and subjects were osteoarthritis patients in rheumatology clinic of Sardjito general hospital. Body mass index and visual analogue scale (VAS) score were measured. Correlation between BMI and VAS score were analyzed by bivariate correlation test.Results: There were 80 patients with osteoarthritis who participated in the study. Mean BMI was 26.36 +4.23 kg/m2 and VAS score was 52.40+24.53 mm. The correlation test showed that there was a positive but non significant correlation between BMI and VAS scores (r = 0,11; p = 0,33).Conclusion: There was a positive but non significant correlation between body mass index and the severity of joint pain in knee osteoarthritis.